2020
DOI: 10.3389/fchem.2020.00768
|View full text |Cite
|
Sign up to set email alerts
|

Expedited Transition in the Wettability Response of Metal Meshes Structured by Femtosecond Laser Pulses for Oil-Water Separation

Abstract: Oil-water separation using super-wetting and the selective permeability of membranes for oil or water has great ecological and economic significance. We report on the transition of wettability response, from superhydrophilic underwater-superoleophobic to superhydrophobic-superoleophilic state, by nanostructuring stainless steel and copper meshes using ultrashort femtosecond laser pulses. Our approach is environment-friendly, chemical free, and efficient as it exploits the benefit of aging the processed samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…However, previous work shows that the achieved contact angles cannot be described solely by topographical aspects, which is why the influence of surface chemistry has to be considered (see Question 5). During LIPSS generation in air environment, metals are subject to laser-induced oxide-layer formation, which favors the formation of a hydroxylated layer and is thus responsible for super-hydrophilic properties after laser processing [81].…”
Section: Question 6 How Can the Wettability Of Lipss-covered Surfaces Be Stabilized In The Long Term To Be Reliable In Everyday Life?mentioning
confidence: 99%
“…However, previous work shows that the achieved contact angles cannot be described solely by topographical aspects, which is why the influence of surface chemistry has to be considered (see Question 5). During LIPSS generation in air environment, metals are subject to laser-induced oxide-layer formation, which favors the formation of a hydroxylated layer and is thus responsible for super-hydrophilic properties after laser processing [81].…”
Section: Question 6 How Can the Wettability Of Lipss-covered Surfaces Be Stabilized In The Long Term To Be Reliable In Everyday Life?mentioning
confidence: 99%
“…Fig. 12 showed the separation efficiencies of superhydrophobic stainless steel surfaces obtained from different methods [48] , [52] , [53] , [54] . It was indicated that the separation efficiency of the as-prepared samples ranked among the highest values reported before.…”
Section: Resultsmentioning
confidence: 99%
“…The role of low-pressure and vacuum ageing was also tested. Complex geometrical form and curved nature of meshes is crucial and not easy by itself and it was already demonstrated in [6]. In our work we focused on influence of processing atmosphere and subsequent long-term ageing on the wetting behaviour of laser treated meshes.…”
Section: Introductionmentioning
confidence: 95%
“…Stainless steel in form of meshes is a robust, durable and flexible construction material. Recently, controlling the wettability state of the metal meshes by femtosecond laser-induced structuring has found applications for efficient oil-water separation [5,6]. Wetting is the ability of a liquid medium to maintain contact with a solid medium due to intermolecular interaction when in contact with each other.…”
Section: Introductionmentioning
confidence: 99%